Implementasi Metode Reynolds menggunakan Simulasi Kerumunan Bebek - Andriyanto, Sidhiq; Suyanto, M.; Sukoco, Sukoco (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2017)
"Simulation of Duck Crows Using Reynolds Method" is a study with the aim to find out the behavior of duck breeding crowd. The next goal is to make a crowd simulation using the Reynolds method. Limitations of this research variable is the object of research on adult duck Turi, the method used is Reynolds method. The simulations are made using Unity3D software in the form of 3D and the animation provided is just a running gesture. The method of analysis of this research is using research and development method. The result of the research is the data of duck walking in the crowd to be applied in 3D animation. The end result of the study is a simulation of duck crowds that run on flat fields. Destination directions are affected by mouse input and can avoid obstacles when walking. This simulation uses Reynolds basic rules of cohesion, alignment and separation.The conclusion of the research is that there is a similarity between the simulation of the crowd with the movement of the original duck crowd and the Reynolds method can be applied in the simulation of the duck crowd in 3D. Research produces 3D animation of duck crowds that are given the ability to avoid obstacles and target goals determined by mouse input.